Challenging the Dominant Narrative: Critical Bilingual Leadership (Liderazgo) for Emergent Bilingual Latin@ Students - Wiemelt, Joseph; Welton, Anjale (International Journal of Multicultural Education, 2015)
The growing “Latinization” of the United States is drastically changing the demographics of the students served in PK-12 public schools (Irizarry, 2011). To understand how educational leaders can best serve this changing student demographic, we use Critical Bilingual Leadership, i.e. Liderazgo, to interrogate institutional and structural racism through the use of the testimonios of members of a school community that aim to create a culturally and linguistically responsive school. We found that liderazgo was operationalized across the following themes: dual language programming as the foundation for equity; drawing on experiential knowledge as a strength; fostering relationships through transcaring; and instructional bilingual leadership. <!–EndFragment–> <!–EndFragment–>